Humor Facilitates Text Comprehension: Evidence from Eye Movements. Issue 4 (19th May 2017) - Ferstl, Evelyn C.; Israel, Laura; Putzar, Lisa
Abstract : One crucial property of verbal jokes is that the punchline usually contains an incongruency that has to be resolved by updating the situation model representation. In the standard pragmatic model, these processes are considered to require cognitive effort. However, only few studies compared jokes to texts requiring a situation model revision without being funny. In the present study participants' eye movements were recorded while they read short texts falling into four categories: jokes, texts that made a revision of the situation model necessary without being funny (revision texts), and two types of control texts. Jokes were read faster and elicited fewer regressive eye movements than the other text categories. Women were more sensitive to revision and inference demands of nonhumorous texts than men, and this was particularly the case when the instructions required a meta-linguistic evaluation. In contrast to the predictions of the two-stage model of pragmatics, humor appreciation facilitated text comprehension, and this effect was more pronounced for men than for women.